DALIHAN NATOLU ROLE IN TRADITIONAL MARRIAGE PORTLAND, OREGON SEKAR ROSE COUNTRY VILLAGE OF SAND TURTLE INDRAGIRI UPSTREAM - Tamba, Mega Veronika Tamba Veronika; ', Isjoni; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The party marriage ceremony is the most important thing for the people of Batak. The wedding is the bridge that brings Na Tolu from parents bride with Na Tolu from parents of the bride. The purpose of this study was to investigate the Marriage Procedure Toba Batak society, to understand the function and role of Na Tolu Batak Toba traditional wedding in the village of Pasir Penyu District Roses Flower District IV, to find out people's views on the village of Roses Flower Dalihan function and role Natolu Village Flower Rose District of Pasir Penyu district Kite, Dalihan Natolu To determine the role as a mediator for the resolution of problems in the marriage Batak Toba. The method used is descriptive qualitative. When the study began filing title until the completion of a revised proposal last essay writer. The results of this study indicate that Natolu Dalihan role in marriage Batak Toba indigenous peoples is a matter that can not be separated during a traditional wedding ceremony held valid by tradition Toba Batak society. Keywords: Role, Dalihan Natolu, marriage, Batak Toba, Flower Rose